Determinants of general health status and specific diseases of elderly women and men: A longitudinal analysis for Western and Eastern Germany - Christian Wegner; Marc Luy (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2009)
We used the panel data of the German Life Expectancy Survey (LES) for analysing the impact of specific life conditions on the gender-specific health outcome of respondents aged 60+ at follow-up over a period of 13 years (for western Germany) and 7 years (for eastern Germany) respectively. For western Germany we extended the analysis by additional information about life course experiences with unemployment, smoking behaviour, reproduction history and migration background. We analysed self-rated general health as well as the self-reported absence and prevalence of specific diseases which are directly related to the main causes of death and disabilities. Moreover, we analysed death and attrition as competing risks at follow-up in order to control for selection effects to the health outcome. The analysis was separated by sex to account for gender-specific life conditions. The results confirm existing knowledge regarding socioeconomic differences and offer insights into the influence of health lifestyles, in particular sports activity and smoking history. Further, associations were found between the earlier presence of diseases and the health condition at follow-up. Gender differences in health outcomes are partly explained by the higher mortality of males and the higher number of non-respondents among females. The study extends the knowledge about risk factors for health in Germany by a longitudinal approach and emphasises the importance of earlier life stage intervention to reduce disease-specific risk factors.
Keywords: 300; Health; subjective health; disease; health transition; western and eastern Germany; longitudinal analysis; gender; ageing; life course; health; subjective health; disease; health transition; western and eastern Germany; longitudinal analysis; gender; ageing; life course